Clinical pattern, mutations and in vitro residual activity in 33 patients with severe 5, 10 methylenetetrahydrofolate reductase (MTHFR) deficiency - Huemer, Martina; Trefz, Friedrich K. (Journal of inherited metabolic disease, 2016)
Background Severe methylenetetrahydrofolate reductase (MTHFR) deficiency is a rare inborn defect disturbing the remethylation of homocysteine to methionine (<200 reported cases). This retrospective study evaluates clinical, biochemical genetic and in vitro enzymatic data in a cohort of 33 patients. Methods Clinical, biochemical and treatment data was obtained from physicians by using a questionnaire. MTHFR activity was measured in primary fibroblasts; genomic DNA was extracted from cultured fibroblasts. Results Thirty-three patients (mean age at follow-up 11.4 years; four deceased; median age at first presentation 5 weeks; 17 females) were included. Patients with very low (<1.5 %) mean control values of enzyme activity (n = 14) presented earlier and with a pattern of feeding problems, encephalopathy, muscular hypotonia, neurocognitive impairment, apnoea, hydrocephalus, microcephaly and epilepsy. Patients with higher (>1.7-34.8 %) residual enzyme activity had mainly psychiatric symptoms, mental retardation, myelopathy, ataxia and spasticity. Treatment with various combinations of betaine, methionine, folate and cobalamin improved the biochemical and clinical phenotype. During the disease course, patients with very low enzyme activity showed a progression of feeding problems, neurological symptoms, mental retardation, and psychiatric disease while in patients with higher residual enzyme activity, myelopathy, ataxia and spasticity increased. All other symptoms remained stable or improved in both groups upon treatment as did brain imaging in some cases. No clear genotype-phenotype correlation was obvious. Discussion MTHFR deficiency is a severe disease primarily affecting the central nervous system. Age at presentation and clinical pattern are correlated with residual enzyme activity. Treatment alleviates biochemical abnormalities and clinical symptoms partially.
Published online: 30 May 2015
Gesehen am 02.06.2020